2014
DOI: 10.1038/onc.2014.121
|View full text |Cite
|
Sign up to set email alerts
|

Cooperation of Blm and Mus81 in development, fertility, genomic integrity and cancer suppression

Abstract: BLM is a DNA helicase important for the restart of stalled replication forks and for homologous recombination (HR) repair. Mutations of BLM lead to Bloom Syndrome, a rare autosomal recessive disorder characterized by elevated levels of sister chromatid exchanges (SCEs), dwarfism, immunodeficiency, infertility and increased cancer predisposition. BLM physically interacts with MUS81, an endonuclease involved in the restart of stalled replication forks and HR repair. Herein we report that loss of Mus81 in Blm hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 55 publications
0
12
0
Order By: Relevance
“…The study has demonstrated that infertile men with various semen parameters exhibited a significantly high level of mean SCE (Papachristou et al, ); however, nonsmokers were not included. An elevated level of SCE frequency and infertility is also involved in the pathophysiology of Bloom syndrome which is an autosomal recessive disorder (El Ghamrasni et al, ). Studies mentioned above have demonstrated that SCE is associated with smoking and malefactor infertility; therefore, smoking‐induced SCE may be one of the reasons of infertility in men.…”
Section: Cigarette Smoking and Genetic Alterationsmentioning
confidence: 99%
“…The study has demonstrated that infertile men with various semen parameters exhibited a significantly high level of mean SCE (Papachristou et al, ); however, nonsmokers were not included. An elevated level of SCE frequency and infertility is also involved in the pathophysiology of Bloom syndrome which is an autosomal recessive disorder (El Ghamrasni et al, ). Studies mentioned above have demonstrated that SCE is associated with smoking and malefactor infertility; therefore, smoking‐induced SCE may be one of the reasons of infertility in men.…”
Section: Cigarette Smoking and Genetic Alterationsmentioning
confidence: 99%
“…In mice, the requirements of HSP90AA1, MAPK1 and PRMT5 for spermatogenesis have been shown, and the absence of one of these genes leads to germ cell reduction or inhibition of proliferation (Grad et al, ; Thuillier et al, ; Wang et al, ). However, studies on some p53‐related genes, such as BLM and SUMO3, have demonstrated that a deficiency in one gene does not cause infertility (El Ghamrasni et al, ; Wang et al, ). These genes are necessary factors whose deficiency sensitises germ cells to DNA damage rather than exerting direct effects.…”
Section: Discussionmentioning
confidence: 99%
“…These genes are necessary factors whose deficiency sensitises germ cells to DNA damage rather than exerting direct effects. Blm −/− or Mus81 −/− single‐mutant mice do not exhibit sterility, but Blm −/− Mus81 −/− double‐mutant mice show a severe reduction in spermatogonial germ cells (El Ghamrasni et al, ). Sumo3 −/− mice also appear to have no defect in fertility (Wang et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Joint molecule structures that may differ from Holliday junctions are formed during replication restart [84]. Holliday junctions have to be resolved before anaphase; otherwise, chromatid nondisjunction or breakage will occur [84][85][86]. There are four evolutionarily conserved pathways that deal with Holliday junctions or similar joint molecules (illustrated in Figure 1a and reviewed in [87]).…”
Section: Resolution Of Holliday Junctionsmentioning
confidence: 99%